2001
DOI: 10.1021/tx000216e
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Study on the Quinone/Quinone Methide Chemistry of Flavonoids

Abstract: A structure-activity study on the quinone/quinone methide chemistry of a series of 3',4'-dihydroxyflavonoids was performed. Using the glutathione trapping method followed by HPLC, (1)H NMR, MALDI-TOF, and LC/MS analysis to identify the glutathionyl adducts, the chemical behavior of the quinones/quinone methides of the different flavonoids could be deduced. The nature and type of mono- and diglutathionyl adducts formed from quercetin, taxifolin, luteolin, fisetin, and 3,3',4'-trihydroxyflavone show how several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
1
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(137 citation statements)
references
References 35 publications
7
125
1
4
Order By: Relevance
“…As recently reported, o-quinone trapping method by glutathione appeared to be an accurate method for quantification of o-quinone metabolites (Awad et al, 2000;Boersma et al, 2000;Awad et al, 2001;Awad et al, 2002a,b). In these studies, the method proved useful for analysing the nature and biochemical behavior of quercetin o-quinone, and characterization of its p-quinone methide isomers (Awad et al, 2000;Boersma et al, 2000;Awad et al, 2001;Awad et al, 2002a,b). According to these authors, for quercetin o-quinone and p-quinone methide III, glutathione adducts can be formed only at C2´, C5´, and C6´, whereas for pquinone methides I and II, adduct formation at C2´, C5´, C6´, C6, and C8 is possible Awad et al, 2001).…”
Section: Reactions At the Reactive Side Chains Of Proteins: Amino- Smentioning
confidence: 74%
See 3 more Smart Citations
“…As recently reported, o-quinone trapping method by glutathione appeared to be an accurate method for quantification of o-quinone metabolites (Awad et al, 2000;Boersma et al, 2000;Awad et al, 2001;Awad et al, 2002a,b). In these studies, the method proved useful for analysing the nature and biochemical behavior of quercetin o-quinone, and characterization of its p-quinone methide isomers (Awad et al, 2000;Boersma et al, 2000;Awad et al, 2001;Awad et al, 2002a,b). According to these authors, for quercetin o-quinone and p-quinone methide III, glutathione adducts can be formed only at C2´, C5´, and C6´, whereas for pquinone methides I and II, adduct formation at C2´, C5´, C6´, C6, and C8 is possible Awad et al, 2001).…”
Section: Reactions At the Reactive Side Chains Of Proteins: Amino- Smentioning
confidence: 74%
“…In these studies, the method proved useful for analysing the nature and biochemical behavior of quercetin o-quinone, and characterization of its p-quinone methide isomers (Awad et al, 2000;Boersma et al, 2000;Awad et al, 2001;Awad et al, 2002a,b). According to these authors, for quercetin o-quinone and p-quinone methide III, glutathione adducts can be formed only at C2´, C5´, and C6´, whereas for pquinone methides I and II, adduct formation at C2´, C5´, C6´, C6, and C8 is possible Awad et al, 2001). Translating this information to our case and consequently in accordance to the observed decrease in the nucleophilic protein side chains, similar covalent adduct formation at the proposed C atoms for the flavonoids is possible.…”
Section: Reactions At the Reactive Side Chains Of Proteins: Amino- Smentioning
confidence: 99%
See 2 more Smart Citations
“…In the light of the indications of its potential nephrotoxicity demonstrated in that trial, we tested the potential of quercetin to undergo biotransformation via conjugation with glutathione (GSH) to a proximate nephrotoxicant, analogous to the nephrotoxicity associated with hydroquinone (Peters et al, 1997), bromohydroquinone (Monks et al, 1985), 17b-estradiol (Butterworth et al, 1997) or haloalkenes (Iverson et al, 1996). Previous reports have indicated that GSH conjugates are formed in vitro (Awad et al, 2000(Awad et al, , 2001Boersma et al, 2000;Galati et al, 2001). Furthermore, mindful of the fact that COX activity is a potential mechanistic target of quercetin, we compared its effect on cellular prostaglandin E-2 (PGE-2) production with that of representative quercetin metabolites.…”
mentioning
confidence: 99%